In vivo effects of South African traditional medicines against Mycobacterium tuberculosis in experimental mice - Bapela, Nchinya Benedict (Division of Clinical Immunology, 2017)
Although it is more than 100 years since Robert Koch discovered the tubercle bacillus, and more than 40 years since effective chemotherapy became available, the incidence of tuberculosis is increasing in much of the developing world and has recently re-emerged as a public health problem in industrialized countries. This problem is compounded by the increase in host susceptibility to tuberculosis caused by co-infection with HIV (Human Immunodeficiency Virus) and the emergence of Mycobacterium tuberculosis strains that are resistant to the front-line drugs. These factors highlight the urgent need for development of new drug classes to counter the threat posed by tuberculosis. The purpose of the present study was to develop a mouse model for Mycobacterium tuberculosis with the aim of determining the antimycobacterial activity of medicinal plants used by traditional doctors to treat tuberculosis in South Africa. Furthermore, the toxic effects of these medicinal plants in uninfected mice were determined. A field trip to the Northern Cape, Western Cape, Eastern Cape and Free State provinces was undertaken and medicinal plants used by traditional doctors to treat tuberculosis or its symptoms were collected, identified and examined for their therapeutic effects against Mycobacterium tuberculosis, determined using the mouse model. In addition, the effects of medicinal plants on the production of cytokines and granuloma formation in infected mice were examined. Six-to-ten week old C57BL/6 mice were infected with 107 viable Mycobacterium tuberculosis H37Rv strain by an aerosol exposure model. Bacterial growth was monitored by sacrificing infected but untreated mice at day 1, week 2 and week 4. Treatment with medicinal plant extracts was started 2 weeks after infection and continued for 2 weeks. An INH-RIF combination was used as positive controls. The bacterial load in infected but untreated mice increased by 1 log unit each week for 2 to 3 weeks. Bacterial loads were not detected in INH-RIF treated mice after 2 weeks of treatment. Treatment of mice with high doses of plant extracts was toxic. None of the tested medicinal plant extracts showed any activity against Mycobacterium tuberculosis. The production of IL-12 at week 4 was suppressed/ decreased when plant extract A was given at different concentrations. The bacterial loads in the lungs of the plant extract A treated mice was higher than that of the untreated mice (p < 0.005). Histological analysis of the lungs also revealed a high number of bacilli and increased size of the formed granuloma. In conclusion, the selected plant extracts obtained by water extraction exhibited no anti-tuberculosis activity in the laboratory mouse model for Mycobacterium tuberculosis infection. Furthermore, it was also shown that some plant extracts suppressed the production of IL-12, which plays an important role in the host's defense against Mycobacterium tuberculosis. However, further work is required to test if treatment for longer periods exhibits antituberculous activity.